Avaliação do desempenho do agente coagulante obtido a partir da Moringa Oleifera Lam para tratamento de água produzida - Jesus, Felipe Abreu de (2018)
At some point, the activity in a petroleum well will begin to produce water. This happens according to the conditions of the reservoir, the age of the productive wells, or the need to use water injectors to increase the productivity of the hydrocarbons. The produced water, together with the petroleum, is then pushed up to the surface along with an array of other contaminants, which, before being conditioned for disposal, need to pass through a series of treatments. Among these is coagulation, an important stage in the removal of the organic and inorganic materials. The use of natural coagulants presents itself as a promising alternative to the treatment of water, and has proved advantageous in relation to the inorganic coagulants, specifically in relation to biodegradability, low toxicity, and a low index of residual mud production. The Moringa oleifera Lam possesses cationic proteins in its seeds that have coagulating properties, thus being able to be used to substitute chemical coagulants like aluminum sulfate. As such, this work’s objective is to evaluate the performance of the coagulating agent for the treatment of water produced by petroleum using the extract from seeds of the Moringa oleifera Lam plant. In the tests, the water utilized was synthetic produced water together with petroleum taken from the oilfield in Carmópolis/SE. First, the BSW, the specific mass, the ºAPI, and the viscosity of the oil used for the preparation of synthetic produced water (SPW) was determined. After the analysis of the petroleum, the centesimal metrics of the seeds were determined: humidity, ash, lipids by extraction with Soxhlet and proteins, using the Kjeldahl method. After, coagulation/flocculation tests were conducted in order to evaluate the different preparation methods of the moringa coagulating agent in the reduction of the oil and gravel content (OGC). These experiments were conducted using the jar test, varying the concentration of the Moringa oleifera Lam between 50 ppm and 300 ppm. The data obtained via the 7 preparation methods were submitted to variance analysis (ANOVA) and the Tukey test, with a 95% rate of probability to verify if there was a significant difference or not among the concentrations and methods. In the analysis of the petroleum, the values found were: 0,7% or BSW, 0,899 g/cm3 of the specific mass, 25,85 of the ºAPI and 699, 228, 173, and 127 cP of viscosity in the following temperatures: 20, 40, 50 and 60 ºC, in that order. The results obtained for the centesimal composition of the moringa seed showed a high lipid content (26%) and proteins (45%) and a low humidity content (6,82%), ash (3,47%) and carbohydrates (7,31%). In conclusion, then, the moringa seed as a natural coagulating agent has a potential to remove the OGC, which can be considered an alternative for the treatment of water produced by petroleum.